Voice from the front-line - Rose-Martland, Jeff (Henry Stewart Talks, 2009)
Simple contact center organization, Types of contact centers, Why have agents?, What are agents?, Reality, Dehumanization, Quality evaluation, Frustration, Contact center survival plan